Binge drinking and psychoactive drug use in a cohort of European youths - Roberta Siliquini; Alessandra Colombo; Paola Berchialla; Fabrizio Bert; TEN-D Group (SAGE Publishing, 2012)
Background. TEN-D by Night is an international, multicentre, cross-sectional portal survey conducted on a large sample of young people in six European countries. This paper aims to investigate the alcohol and psychoactive drug consumption of this sample, with a focus on the prevalence of binge drinking and the poly-drug habits of the TEN-D cohort. Design and Methods. The study population consisted of 4695 young people attending recreational sites on weekend nights. The intervention included two questionnaires and two psychoactive substance detection tests performed at the entry and exit of the recreational sites. A multivariate logistic regression model was used to predict the probability of binge drinking. Results. Binge drinking was reported by 20% of the males and 13% of the females (P=0.001) before entry into the recreational sites and by 18% of the males and 11% of the females before entry into the clubs (P<0.001). Poly-drug use was reported by 71% of the males and 66% of the females. Living with a parent (OR 1.57; P=0.01), seeking employment (OR 1.66; P=0.005) and cannabis consumption (several times per month and several times per week, OR 1.94 and 3.66, respectively, P<0.05) were associated with binge drinking. Conclusions. Our survey showed that it is possible to identify individuals and groups at higher risk of binge drinking. This identification would allow for a focus on specific targets and would facilitate the redesign of prevention programmes. The increased use of psychoactive substances among youths should be studied extensively to promote successful prevention campaigns.